Quantitative Affinity Determination by Fluorescence Anisotropy Measurements of Individual Nanoliter Droplets - Gielen, Fabrice; Butz, Maren; Rees, Eric J; Erdelyi, Miklos; Moschetti, Tommaso; Hyvönen, Marko; Edel, Joshua B; Kaminski, Clemens F; Hollfelder, Florian (Analytical chemistry (Washington), 2017)
Fluorescence anisotropy measurements of reagents compartmentalized into individual nanoliter droplets are shown to yield high-resolution binding curves from which precise dissociation constants (K d) for protein–peptide interactions can be inferred. With the current platform, four titrations can be obtained per minute (based on ∼100 data points each), with stoichiometries spanning more than 2 orders of magnitude and requiring only tens of microliters of reagents. In addition to affinity measurements with purified components, K d values for unpurified proteins in crude cell lysates can be obtained without prior knowledge of the concentration of the expressed protein, so that protein purification can be avoided. Finally, we show how a competition assay can be set up to perform focused library screens, so that compound labeling is not required anymore. These data demonstrate the utility of droplet compartments for the quantitative characterization of biomolecular interactions and establish fluorescence anisotropy imaging as a quantitative technique in a miniaturized droplet format, which is shown to be as reliable as its macroscopic test tube equivalent.